2017
DOI: 10.1515/pjmpe-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Gamma Index for Quality Assurance of Simultaneously Integrated Boost (SIB) IMRT Plans for Head and Neck Carcinoma

Abstract: Objective: The Gamma Index is prerequisite to estimate point-by-point difference between measured and calculated dose distribution in terms of both Distance to Agreement (DTA) and Dose Difference (DD). This study aims to inquire what percentage of pixels passing a certain criteria assure a good quality plan and suggest gamma index as efficient mechanism for dose verification of Simultaneous Integrated Boost Intensity Modulated Radiotherapy plans. Method: In this study, dose was calculated for 14 head and neck … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Then, all the fields were combined to get an image on a composite field with a threshold of 10 %. The composite field was analyzed with the same DD/DTA criteria at ≥ 90 % of the total pixels [20,21].…”
Section: Planning and Measuring Qa Pretreatmentmentioning
confidence: 99%
“…Then, all the fields were combined to get an image on a composite field with a threshold of 10 %. The composite field was analyzed with the same DD/DTA criteria at ≥ 90 % of the total pixels [20,21].…”
Section: Planning and Measuring Qa Pretreatmentmentioning
confidence: 99%
“…The figure illustrated the hot spots (>107% and <115% isodose areas) in the IMRT plan and the localization of "failing points" in γ analysis overlaid on CT anatomy is depicted. In a study with simultaneously integrated boost (SIB) IMRT, it was found that failed data points predominantly lie in high-dose gradient regions [16]. The "hot" or "cold" region situated over the target could have a different significance than a normal organ [17].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested using a combination of the average gamma, maximum gamma and the percentage gamma passing rate to analyse dose distributions and to make judgements regarding the agreement between measurements and calculation based on clinically driven criteria. 22,23,47,48,51,[55][56][57] According to Miften et al, 48 the analysis of the maximum gamma and the average gamma should be considered together with the percentage gamma passing rate for pre-treatment plan QA. Our data suggest an overall mean γ ave ≤ 0•19 for 3 mm/1-3%, ≤ 0•27 for 2 mm/1-3% and ≤ 0•49 for 1 mm/1-3%; and an overall mean γ max ≤ 2•63 for 3 mm/ 1-3%, ≤ 2•87 for 2 mm/1-3% and ≤ 3•58 for 1 mm/1-3% for patient-specific intracranial SRS/SRT VMAT pre-treatment QA using the portal dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…van Zijtveld et al 58 also performed gamma analysis using a gamma criterion of 3%/3 mm and reported a mean γ ave value of 0•43 ± 0•13 for 75 patients pre-treatment plan QA. Similarly, Atiq et al 57 evaluated pre-treatment IMRT QA for 14 head and neck patients' treatment plans using the gamma analysis to investigate gamma criteria that assures a good quality plan and reported mean γ max of 2•66 ± 2•38 and mean γ ave of 0•30 ± 0•07 for 3 mm/5% gamma criterion.…”
Section: Discussionmentioning
confidence: 99%